Effect of refermentation conditions and microoxygenation on the reduction of volatile acidity by commercial S. cerevisiae strains and their impact on the aromatic profile of wines - Moura, A. Vilela (2010)
Herein, we evaluate the applicability of previously characterized commercial and indigenous Saccharomyces cerevisiae strains and non-S. cerevisiae species for the deacidification of white and red wines at a pilot scale. The effect of the refermentation process (mixture of acidic wine with musts from freshly crushed grapes or with residual marc) as well as MO (MO) on acetic acid removal efficiency and wine aromatic composition was also assessed in a red wine. The commercial strains S26 and S29 efficiently reduced both acetic acid (43 and 47 %, respectively) and sugar (100 %) after 264 hours of refermentation of an acidic white wine that was supplemented with grape must. Similar results (60-66 % of acetic acid removal) were observed for red wine deacidification using grape must, independently of MO. When residual marc was used for deacidification, strain S26 removed 40% of acetic acid, whereas strain S29 did not initiate refermentation with or without MO. Wines obtained by refermentation with the must had significantly lower acetic acid and a higher total SO2 concentration in comparison to the wines deacidified by the grape marcs. The volatile aroma compound´s composition of deacidified red wines was dependent on the refermentation process used, rather than on MO. The marc-deacidified wine obtained by the use of strain S26 and without MO achieved the best sensory classification. When data from all analytical and sensory evaluation were combined, Principal Component Analysis (PCA) separated the wines into three distinct groups according to the strain and the refermentation process independently of MO. We successfully established an efficient and cheap enological solution for the rectification of volatile acidity of wines.